2007
DOI: 10.1061/(asce)0733-9429(2007)133:8(896)
|View full text |Cite
|
Sign up to set email alerts
|

Double-Averaged Open-Channel Flows with Small Relative Submergence

Abstract: We investigate the turbulent structure of shallow open channel flows where the flow depth is too small ͑compared with the roughness height͒ to form a logarithmic layer but large enough to develop an outer layer where the flow is not directly influenced by the roughness elements. Since the log layer is not present, the displacement height d, which defines the position of the zero plane, and the shear velocity u * cannot be found by fitting the velocity data to the log law. However, these parameters are still ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
82
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 17 publications
16
82
3
Order By: Relevance
“…This methodology relies on an averaging procedure which follows two steps: ͑i͒ time averaging is applied in order to compute flow statistics for each measurement point contained within the flow regions captured by PIV; ͑ii͒ flow statistics resulting from time averaging are spatially averaged along thin boxes parallel to the bed. 18 The streamwise extent of such boxes is one bead diameter and, in the lateral direction, they include measurement points located in the top and valley section. By virtue of the PIV methodology the thickness of the averaging boxes is equal to the height of the interrogation areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology relies on an averaging procedure which follows two steps: ͑i͒ time averaging is applied in order to compute flow statistics for each measurement point contained within the flow regions captured by PIV; ͑ii͒ flow statistics resulting from time averaging are spatially averaged along thin boxes parallel to the bed. 18 The streamwise extent of such boxes is one bead diameter and, in the lateral direction, they include measurement points located in the top and valley section. By virtue of the PIV methodology the thickness of the averaging boxes is equal to the height of the interrogation areas.…”
Section: Resultsmentioning
confidence: 99%
“…This allowed to have enough measurement detail to estimate spatially averaged flow statistics. 18 For each experiment, 2200 images were recorded at a sampling frequency of roughly 13 Hz. The random error of a PIV measurement was estimated to be ⌬v = 0.0025 m / s. It was computed as ⌬v = ⌬s / ⌬t, where ⌬s corresponds to 1/10 of 1 pixel physical dimension, and ⌬t is the time delay between the subsequent images.…”
Section: A Surface Flow Measurementsmentioning
confidence: 99%
“…Indeed, Gimenez-Curto and Corniero (1996) and Gimenez-Curto and Corniero Lera (2003) suggested that at very low submergences the form-induced stress could become the dominant component in the streamwise momentum balance. Interestingly Manes et al (2007) found that the relative contribution of form-induced stress increased as submergence decreased in their experiments on open channel flow over closely-packed spheres.…”
Section: Introductionmentioning
confidence: 98%
“…Nikora (2009) extended the use of the double-averaging methodology to develop a theoretical expression that explicitly showed that the friction factor can be accounted for by six additive components, of which only three are present in two-dimensional uniform spatially-averaged flow without secondary currents: viscous stress, turbulent stress and forminduced stress. The contribution of the form-induced stress, ũw , has recently attracted substantial attention as it has been shown to play an important role in the overall streamwise momentum balance in the near-bed region (Aberle, Koll, & Dittrich, 2008;Dey & Das, 2012;Ferreira et al, 2010;GimenezCurto and Corniero, 1996;Gimenez-Curto and Corniero Lera, 2003;Manes, Pokrajac, Coceal, & McEwan, 2008;Manes, Pokrajac, & McEwan, 2007;Manes, Pokrajac, McEwan, & Nikora, 2009;Mignot, Barthelemy, & Hurther, 2009a,b;Nikora et al, 2007b;Sarkar & Dey, 2010). Indeed, Gimenez-Curto and Corniero (1996) and Gimenez-Curto and Corniero Lera (2003) suggested that at very low submergences the form-induced stress could become the dominant component in the streamwise momentum balance.…”
Section: Introductionmentioning
confidence: 99%
“…'u=}R@; OWQ QO QwmPt |=yQ=DN=U C}ty= R= |m =L QDO}OH |=yxar=]t 'u}vJty 'Qo}O hQ] R= [7] "CU=yxv=NwQ QO |y=}o VWwB CmQL w '|v=mt`}RwD |xwLv w x@ [3] "OvDUy |SQv= Q=W@; Ov}=Qi [12] "OQm ZQi C@=F = Q =yu; u=wD|tv , qta |tD} Q=or p}iwQB x@ OwOLt |@Uv j= QeDU= QF= xm CU= xOW xOy=Wt [13] [17] "CU= xOy=Wt p@=k =}r=D}= QwWm |v=DUywm |=yxv=NOwQ |RmQt VN@ QO x} wv=F |=yu=}QH xHwD p@=k Q}F -=D sOa Qov=}@ xm 'CU= 5 R= QD |xrY=i QO |@v=H |=yxQ=w}O R= QwO |}x}L=v QO =y|Q}oxR=Ov= [2] "CU= u=}QH [3] %OQw; CUO x@ 5 w 4 |=yx]@= Q ltm =@ = Q |oDiW; nQR@ [2] " CU= p=v=m QO 12 ?wQ=H u=tRty w VyH u=}QH |}q=@ \=kv x@ QDU@ |m}ORv QO u} =B CaQU =@ u=}QH [22] 'OvDUy p=v=m QDU@ CtU x@ QDU@ R= QwO w q=@ CaQU =@ u=}QH |r=kDv= CmQL xO}OB wO u}= CmQL xm =Hv; R= "OvwW|t s =k |=DU= Q QO |oDU@ty V}=Ri= ?Hwt \N =@ h= QLv= |x}w= R 'CU= x= Qty u=}QH CUOu} =B CtU x@ CmQL =@ u=tRsy QO [9] "OwW|t O=H}= 'CU= xOW xO=O V}=tv …”
mentioning
confidence: 99%